2021
DOI: 10.1155/2021/6698522
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Prognosis, and Long-Term Response to Ranibizumab of Macular CNVs in Pattern Dystrophies Spectrum: A Pilot Study

Abstract: Introduction. To analyze the morphological and functional features of choroidal neovascularizations (CNVs) in eyes affected by pattern dystrophies (PD), evaluating their long-term response to intravitreal ranibizumab, and comparing them with CNVs in age-related macular degeneration (AMD). The mean goal is to identify possible disease biomarkers and to evaluate the long-term prognosis of CNVs in PD. Materials and Methods. A retrospective study of 42 patients with naïve CNV (26 PD and 16 AMD), for a total of 47 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Initially, it was hypothesized that the metabolic byproducts may accumulate after the RPE digests the mutant PRPH2 proteins, which may disrupt the extracellular matrix that helps maintain the barrier against CNV [ 14 ]. However, Casilo et al [ 15 ] revealed that the PD subgroup showed thicker choroidal thickness both centrally and underneath the neovascular lesion in contradistinction to the AMD subgroup. Presumably, the thickening of the outer retinal vessels in the Haller layer could cause secondary damage to the overlying choriocapillaris network and induce ischemic phenomena responsible for neovascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, it was hypothesized that the metabolic byproducts may accumulate after the RPE digests the mutant PRPH2 proteins, which may disrupt the extracellular matrix that helps maintain the barrier against CNV [ 14 ]. However, Casilo et al [ 15 ] revealed that the PD subgroup showed thicker choroidal thickness both centrally and underneath the neovascular lesion in contradistinction to the AMD subgroup. Presumably, the thickening of the outer retinal vessels in the Haller layer could cause secondary damage to the overlying choriocapillaris network and induce ischemic phenomena responsible for neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the pilot study performed by Casillo et al [ 15 ], a comparison between the long-term response to intravitreal ranibizumab among patients with PD-associated CNV and CNV in AMD, showed that eyes with PD had a poorer long-term response and greater tendency to atrophic evolution of the disease. Therefore, it is suggested that CNV associated with PD should not be “overtreated” to avoid further atrophic effects.…”
Section: Discussionmentioning
confidence: 99%